PENGARUH PENGGUNAAN MEDIA AJAR BERBASIS TEKNOLOGI ANIMAKER PADA MATA PELAJARAN IPAS TERHADAP MINAT BELAJAR PADA SISWA SEKOLAH DASAR - Erisnaentin, Meilinda; Abdullah, Kusmajid (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
: The effect of using technology-based learning media on science subjects. So you can see how strong the influence of technology-based learning media is on increasing students' interest in learning in the learning process. The aim of this research is to determine the effect of using Animaker technology-based teaching media on class 4 students' interest in learning. This type of research uses a quantitative approach with experimental research methods. The method used to find the effect of treatment on the thing being researched. Therefore, in this experimental method there will be special treatment to determine whether or not there is an influence in the research. The method used by researchers is Quasi Experimental design. hypothesis testing, the results of the independent t test show that there are significant differences between the two groups. Levene's Test shows that the variance of the two groups is considered the same (Sig. 0.804). The t-test results show a t-statistic value of 5.298 with 54 degrees of freedom and a significance value of 0.000. The mean difference between the experimental and control groups was 8.964 with a 95% confidence interval ranging from 5.572 to 12.356. These results indicate that the use of Animaker teaching media significantly increases students' interest in learning compared to conventional learning methods. It is concluded that there is a significant influence from the use of Animaker technology-based teaching media on students' interest in learning in science and science subjects in class 4 at SDN Grogol Utara 09. Analysis statistics show that there is a significant difference in the post-test results between the experimental group using Animaker and the control group using conventional methods. With the experimental group's average post-test results being slightly higher, this difference is statistically large enough to be declared a significant difference.